Scottish youth and antisocial behaviour: a literature review and comparative study - Jelles, Jessica (My University, 2018)
This study intends to address antisocial behaviour in Scottish youth living in Glasgow and investigate whether there is a link between the history of clan system values and youth behaviour. In 2004, the Antisocial Behaviour etc (Scotland) Act 2004 was implemented to deter adults and youth from committing acts considered antisocial. I want to know if the clan structure in Scotland has increased antisocial behaviour in Scottish youth and identify how a youth service is attempting to combat the behaviour. Specifically, the questions this study will address include how the clan system values and beliefs are instilled in the current society and whether it promotes antisocial behaviour, what are the effects of Labelling Theory, if any, whether a youth service in Glasgow is successfully combating the behaviour and if so, how, and how this youth service compares to a youth service in Edmonton, Alberta Canada. Furthermore, Antisocial Behaviour Orders (ASBO’s) are implemented to restrict an individual’s conduct as outlined in the Order, I would like to identify whether the ability for youth to change their behaviour are hindered by these ASBO’s. I will conduct a literature review addressing the issues mentioned, as well as a comparative study of a youth service located in Glasgow and Edmonton. I intend to interview both services in Glasgow and Edmonton to identify what is being done to improve youth behaviour and what Edmonton can learn from Glasgow and vice versa.
Presented on April 23, 2018 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: antisocial behaviour; youth; Scotland